USING REAP (READ, ENCODE, ANNOTATE, PONDER) IN TEACHING READING - Rutela Renette (Universitas Negeri Padang, 2016)
This article aims to explain the use of REAP Strategy in teacing reading. Different reading strategies are needed for different reading purposes. It is aimed to help readers achieve their purposes in reading, whether for gaining information or for pleasure. By using Read, Encode, Annotate and Ponder (REAP) Strategy, it was expected that the students can improve their reading comprehension. It was assumed that Read, Encode, Annotate and Ponder (REAP) was appropriate to overcome the problem. It was because every steps in REAP strategy had some advantages in order to help students understanding a text.